PHOTO CATALITIC ACTIVITY OF Fe3O4/SiO2/TiO2 COMPOSITE BY MECHANO CHEMICALPREPARATION - Didin S. Winatapura; Sari H. Dewi; Siti Wardiati; Adel Fisli (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2015)
PHOTO CATALITIC ACTIVITY OF Fe3O4/SiO2/TiO2 COMPOSITE BY MECHANO CHEMICALPREPARATION. Asimplemechanochemical activation was used to prepare Fe3O4/ SiO2/TiO2 composite. Fe3O4, and SiO2 nanoparticles powder were prepared by co-precipitation method respectively, while TiO2was synthesized by sol-gel method.All of the samples weremixed into vial and milled by wet milling process. The all prepared sampel were characterized by various equipments i.e. X-ray diffractometry (XRD), transmission electron microscope (TEM) and vibrating sample magnetometer (VSM), Fourier transform infrared (FTIR) and UV-Vis Spectrometer. The result shows that Fe3O4/SiO2/TiO2 composite consisted of anatase TiO2 and Fe3O4 phases. The superparamagnetic behavior of Fe3O4 nanoparticle, Fe3O4/ SiO2, and Fe3O4/SiO2/TiO2 composites exhibit the saturationmagnetic (Ms) of 89.43. and 13emu/g, respectively. The particle size of Fe3O4/SiO2/TiO2 composite was distributed in spherical shape and about 100 nm in diameter. Photocatalytic test showed that Fe3O4/SiO2/TiO2 composite can elimininate the methylene blue (MB) dye solution higher than that pure TiO2 commercial product (TiO2M) catalyst. The Fe3O4/SiO2/TiO2 composites can be easily taken back from treated water by using magnetic bar. Keywords: Mechanochemical, Fe3O4/SiO2/TiO2 composite, methylene blue dye, photocatalytic